Cucumber ovaries inhibited by dominant fruit express a dynamic developmental program, distinct from either senescence‐determined or fruit‐setting ovaries. (8th September 2018) - Shnaider, Yula; Mitra, Deblina; Miller, Golan; Baniel, Avital; Doniger, Tirza; Kuhalskaya, Anastasiya; Scossa, Federico; Fernie, Alisdair R.; Brotman, Yariv; Perl‐Treves, Rafael
Summary: Cucurbits represent an attractive model to explore the dynamics of fruit set, whose regulation is not fully understood, despite its importance for yield determination. A fertilized ovary must integrate signals from distant plant parts and 'decide' whether to set fruit, or remain inhibited and later senesce. Here, we set out to characterize first‐fruit inhibition (FFI), that is, the inhibitory effect of the first fruit on subsequent development of younger ovaries during pollination‐induced and parthenocarpic fruit set. After the first fertilized ovaries set fruit, younger fertilized ovaries remained in a temporary state of inhibition. Such ovaries preserved their size and green color, and if the older fruit were removed within a 1‐week reversibility window, they set fruit. The FFI effect was documented in both fertilized and parthenocarpic ovaries. We compared the gene expression profiles of pollinated ovaries (committed to set fruit) with respect to those affected by FFI, and to non‐pollinated ovaries (undergoing senescence). The three fates of the ovaries were characterized by wide changes in gene expression, with several specific transcripts being up‐ or down‐regulated in response to pollination, and to the presence of inhibitory fruit. Metabolic profiling was undertaken and integrated with the transcriptomic data in order to characterize early physiological changes that occur in post‐anthesis ovaries in parthenocarpic and non‐parthenocarpic genotypes. The combined results are discussed with respect to current models of fruit set and specifically with regard to FFI. Moreover, these metabolome and transcriptome data provide a valuable resource for studying ovary development and fruit set. Significance Statement: Inhibition of cucumber fruit set by previous fruit was studied at the metabolic and transcript levels, pointing at a unique developmental fate that still responds to pollination, but also integrates whole‐plant information, to remain in a reversibly inhibited condition. Specific transcription factors, hormone‐ and sugar‐related genes were identified 1 day post anthesis in developing, senescing and inhibited ovaries, respectively, that could play decisive roles in determining each state.